Views of Parents of Children With Down Syndrome on Early Intervention Services in Turkey: Problems, Expectations, and Suggestions. Issue 2 (April 2022) - Tomris, Gozde; Celik, Secil; Diken, Ibrahim Halil; Akemoğlu, Yusuf
Abstract : Perceptions of parents of young children receiving early intervention are important to understand. Parents have valuable opinions on the delivery of early interventions services and can provide critical feedback that can help professionals revise their existing early intervention delivery modalities. In the current study, we examined the perceptions of parents of young children with Down syndrome on early intervention services in Turkey. Specifically, we aimed to understand the parents' views on medical and educational evaluation and diagnosis processes. The study was conducted using a cross-sectional research design, which is one of the survey design methods. Data were collected from a total of 893 parents via an online survey. The results demonstrated that children with Down syndrome were diagnosed within an average of 2.3 months from birth, but the average age for starting education was 10.5 months. The majority of the parents evaluated the process until their children were diagnosed and accessed education services as a rather slow process that proceeded with their own means and efforts. Furthermore, the parents reported that during the diagnosis processes the type of materials, equipment, toys, and settings used were not relevant and time provided was insufficient. Moreover, the majority of the parents reported that the education services presented to them and their children were not sufficient and early intervention services were not provided within a system. As a result, although the legal regulations in Turkey are parallel to those in developed countries and studies in the field have been increasingly gaining momentum, issues such as the absence of an early intervention system model, insufficient cooperation between experts and institutions, and the shortage of expert staff in the field are still present and awaiting a solution.